White vs Green - Weisser, Julie (2021)
Abstract: Urbanization is a world wide phenomenon. Vegetated areas get replaced by dark coloured buildings and increase the heat storage capacity dramatically. Additionally, the human body is vulnerable to heat events which will occur more regularly in the future because of climate change. There are many mitigation strategies that try to adapt the existing infrastructure to the possible natural hazards. One option would be to increase the reflection of solar radiation on surfaces. But is this the most effective way to reduce heat in cities? Or could green roofs have a greater cooling effect on buildings?